Adjustment of photosynthetic activity to drought and fluctuating light in wheat. (27th March 2020) - Grieco, Michele; Roustan, Valentin; Dermendjiev, Georgi; Rantala, Sanna; Jain, Arpit; Leonardelli, Manuela; Neumann, Kerstin; Berger, Vitus; Engelmeier, Doris; Bachmann, Gert; Ebersberger, Ingo; Aro, Eva‐Mari; et al.
Abstract: Drought is a major cause of losses in crop yield. Under field conditions, plants exposed to drought are usually also experiencing rapid changes in light intensity. Accordingly, plants need to acclimate to both, drought and light stress. Two crucial mechanisms in plant acclimation to changes in light conditions comprise thylakoid protein phosphorylation and dissipation of light energy as heat by non‐photochemical quenching (NPQ). Here, we analyzed the acclimation efficacy of two different wheat varieties, by applying fluctuating light for analysis of plants, which had been subjected to a slowly developing drought stress as it usually occurs in the field. This novel approach allowed us to distinguish four drought phases, which are critical for grain yield, and to discover acclimatory responses which are independent of photodamage. In short‐term, under fluctuating light, the slowdown of NPQ relaxation adjusts the photosynthetic activity to the reduced metabolic capacity. In long‐term, the photosynthetic machinery acquires a drought‐specific configuration by changing the PSII‐LHCII phosphorylation pattern together with protein stoichiometry. Therefore, the fine‐tuning of NPQ relaxation and PSII‐LHCII phosphorylation pattern represent promising traits for future crop breeding strategies. Abstract : Elucidating the regulation of photosynthesis under the combination of abiotic stress and fluctuating light is crucial for understanding the plant physiology in realistic conditions and for crop improvement. Wheat copes with drought by reconfiguring the photosynthetic machinery and by slowing down the NPQ relaxation in fluctuating light before photodamage becomes detectable.